2021
DOI: 10.26434/chemrxiv-2021-xq08b-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting the energy-coupling factor (ECF) transporters: identification of new tool compounds

Abstract: The energy-coupling factor (ECF) transporters are a family of transmembrane proteins involved in the uptake of vitamins in a wide range of bacteria. Inhibition of the activity of these proteins could reduce the viability of pathogens that depend on vitamin uptake. Their central role in the metabolism of bacteria and absence in humans make the ECF transporters a potential antibacterial target, which can be further investigated making use of a selective chemical probe. Here, we report on the virtual screening, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…In our previous study, we showed that bacterial cells can be used efficiently to biologically evaluate compounds as potential inhibitors of an ECF transporter. 8 Specifically, an Escherichia coli strain that expresses heterologous ECF FolT2 from L. delbrueckii was used demonstrate on target activity. In the present study, we selected a Gram-positive strain (L. casei) due to its ability to import several essential vitamins such as folic acid, riboflavin, thiamine and biotin from the environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we showed that bacterial cells can be used efficiently to biologically evaluate compounds as potential inhibitors of an ECF transporter. 8 Specifically, an Escherichia coli strain that expresses heterologous ECF FolT2 from L. delbrueckii was used demonstrate on target activity. In the present study, we selected a Gram-positive strain (L. casei) due to its ability to import several essential vitamins such as folic acid, riboflavin, thiamine and biotin from the environment.…”
Section: Resultsmentioning
confidence: 99%
“…casei. 8 We reasoned that the difference in activity may be ascribed either to permeability issues of the compound or to a difference in the amino acid sequence of the ECF transporter between L.…”
Section: Bacterial Uptake Assay Uptake Into Proteoliposomes Medium To High Throughput Low Throughput No Protein Purification Requires Promentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient bioavailability [9] is indispensable for efficient and safe antibiotic therapy, as the requirement for high antibiotic dosage, resulting from poor solubility, enhances the resistance formation of pathogens [10] and commensals [11]. In this work, we prepared a liposomal formulation of a novel compound related to previously reported inhibitors of ECF-transporters [12], HIPS5031 (Figure 1d, comprehensive information on the synthesis and characterization of HIPS5031 is given in the SI). Liposomes are a well-recognized strategy for improving the solubility of lipophilic compounds, which is of increasing significance since the majority of newly developed drugs are considered to be poorly soluble [13].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported a druggability assessment of the ECF-FolT as a novel and attractive antimicrobial target 12 alongside with a set of inhibitors as first tool compounds to explore the ECF transporters from a medicinal chemistry perspective. 13 Since previous studies were limited to tool compounds, we herein present the discovery of another chemical class that inhibits the folate uptake mediated by the ECF-FolT transporter and its further biological evaluation. By combining structure-based virtual screening of our in-house small molecule library and further examination of selected molecules via a Lactobacilius casei whole-cell assay our endeavors revealed in a highly promising hit compound bearing an ureidothiophene carboxylate core motif.…”
Section: Introductionmentioning
confidence: 99%